The Reality of the Application of Solvency 2 in Algerian Insurance Companies - Meriem Sid; Sawsen Zirek (Journal of North African Economies, 2025)
This study aims to shed light on the reality of the Solvency 2 system's application in Algerian insurance companies by highlighting the extent of knowledge of the Solvency 2 requirements of insurance companies operating in Algeria, as well as assessing the level of compliance and responsiveness to the application of the requirements of this system as the most important developments of the precautionary regulations and rules in force internationally. To accomplish this, a questionnaire was designed and distributed to 26 insurance companies operating in the Algerian insurance market, and the data were analyzed using the statistical package for social sciences (SPSS V26). According to the study findings, Algerian insurance companies' awareness of the Solvency 2 application requirements is below the required level, with a disparity in the degree of their responsiveness to Solvency 2 in terms of its three requirements.